GENDER IDENTITY OF MILITARY SERVICE AND THE PROBLEM OF PATRIOTISM - Зикирова Махпрат Солиевна (Journals Park Publishing, 2025)
The article is devoted to the analysis of the relationship between gender identity and patriotism in the context of military service. The article examines the socio-legal and cultural aspects of the formation of patriotic values among military personnel, taking into account gender characteristics. Men and women in the army, as well as the influence of gender stereotypes on military identity pay particular attention to the problems of perception of patriotism. Based on a comparative analysis of domestic and foreign experience, the author substantiates the need for an integrated approach to the education of patriotism in a legal, democratic and social state.